Government support for SMEs in the Fintech Era: Enhancing access to finance, survival, and performance - Najla Abu; Filipa Pires da Silva; Pedro Rino Vieira (Digital Business)
Small and medium-sized enterprises (SMEs) are pivotal to global economic growth and stability but often face considerable barriers in accessing finance for growth and survival. Traditional financial support mechanisms present complexities and challenges, limiting the prosperity of SMEs. This systematic literature review (SLR), underpinned by bibliometric analysis, investigates how financial technology (Fintech) can help overcome these challenges. By analyzing 54 empirical studies, this review examines both the direct and synergistic effects of government support and Fintech innovations on SME financing. Our findings reveal a synergistic relationship between government initiatives and Fintech solutions, proposing transformative strategies that depart from traditional approaches that often separate them. Within the context of recent global economic and regulatory shifts, our study underscores the crucial role of policymakers in creating an enabling environment for SME growth through Fintech. This review addresses a key gap in the literature and provides a foundation for future research on the dynamic relationship between government support and Fintech. It emphasizes their combined capacity to transform SME financial empowerment and contribute to sustainable economic development.